2022
DOI: 10.3390/foods11141999
|View full text |Cite
|
Sign up to set email alerts
|

Attempts to Create Products with Increased Health-Promoting Potential Starting with Pinot Noir Pomace: Investigations on the Process and Its Methods

Abstract: A process for using grape (Pinot noir) pomace to produce products with improved health-promoting effects was investigated. This process integrated a solid–liquid extraction (SLE) method and a method to acylate the polyphenolics in the extract. This report describes and discusses the methods used, including the rationale and considerations behind them, and the results obtained. The study begins with the work to optimize the SLE method for extracting higher quantities of (+)-catechin, (−)-epicatechin and quercet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…Grape pomace is a complex matrix rich in bioactive compounds and macromolecules (hydroxycinnamic acid, hydroxybenzoic acid, flavonoids, fibers) which, once extracted and evaluated for safety, can be used to formulate new products [3,8]. Particularly, extraction processes represent an important step for the identification, isolation, and recovery of active components from grape pomace, such as solid-liquid extraction for recovery of catechin-enriched grape pomace extracts [2,9]. Figure 1 displayed different extraction methods divided into traditional and non-conventional categories allowing the recovery of bioactive molecules (i.e., polyphenols, flavonoids, tannins, organic acids, terpenes, peptides, and polyunsaturated lipids).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Grape pomace is a complex matrix rich in bioactive compounds and macromolecules (hydroxycinnamic acid, hydroxybenzoic acid, flavonoids, fibers) which, once extracted and evaluated for safety, can be used to formulate new products [3,8]. Particularly, extraction processes represent an important step for the identification, isolation, and recovery of active components from grape pomace, such as solid-liquid extraction for recovery of catechin-enriched grape pomace extracts [2,9]. Figure 1 displayed different extraction methods divided into traditional and non-conventional categories allowing the recovery of bioactive molecules (i.e., polyphenols, flavonoids, tannins, organic acids, terpenes, peptides, and polyunsaturated lipids).…”
Section: Introductionmentioning
confidence: 99%
“…Figure 1 displayed different extraction methods divided into traditional and non-conventional categories allowing the recovery of bioactive molecules (i.e., polyphenols, flavonoids, tannins, organic acids, terpenes, peptides, and polyunsaturated lipids). Therefore, grace pomace is considered a promising source for obtaining high-value-added materials due to its antioxidant, antiinflammatory, cardiovascular, anticancer, and antimicrobial properties [8][9][10][11][12][13][14]. In recent years, sustainability has driven and promoted research to enhance and valorize grape pomace to support health and well-being, as the high nutritional profile of this by-product allows it to be used as an ingredient for food enrichment.…”
Section: Introductionmentioning
confidence: 99%
“…The study has demonstrated that the green deep eutectic solvents coupled with a preliminary non-thermal drying could be an effective alternative to traditional processes. Another study has studied the grape pomace extraction and a large scale solid–liquid extraction process was set up to optimize the process and obtain catechin enriched extracts [ 5 ].…”
mentioning
confidence: 99%
“…Inside this by-product, interesting molecules with different biological activities are present. The goal of improving the extraction of these substances is the subject of many studies, including one within this Special Issue [ 5 ]. By-products with important functionality do not come only from winemaking; important molecules are also present in the vine plant.…”
mentioning
confidence: 99%